Keterlibatan Stakeholder dalam Perencanaan Pembiayaan untuk Meningkatkan Mutu Kualitas Pendidikan - Rohayanah; Maman Suryaman (Fakultas Tarbiyah Institut Agama Islam Hamzanwadi Pancor, 2025)
The quality of education is closely linked to the effectiveness of financial planning and management. In this regard, the involvement of various stakeholders plays a critical role in ensuring that educational budgets are allocated and utilized transparently, accountably, and in alignment with actual needs. School committees, parents, and local communities serve as key actors whose participation can enhance the relevance and quality of education. However, in practice, stakeholder engagement often remains superficial or merely administrative, lacking meaningful involvement in planning processes. This study employs a descriptive qualitative approach through literature review to explore the extent to which stakeholder involvement in education financing planning contributes to improving education quality. Findings reveal a gap between the potential and actual roles of stakeholders, largely due to limited capacity, the absence of standard operating procedures, and the lack of open communication forums. Meaningful participation is essential to strengthen social control, increase program effectiveness, and align education with local contexts and needs. Therefore, a collaborative approach is needed—one that includes stakeholders from the initial stages of budgeting to the final evaluation. This paper recommends strengthening stakeholder capacity and developing participatory models to ensure effective and sustainable governance in educational financing. Such efforts are crucial for building an inclusive and accountable education system that truly supports quality improvement in the long term.